Enhancing damage-resistance in low carbon martensitic steels upon dual-pass laser treatment. (February 2021) - Oh, Hyun Seok; Kang, Jiyun; Tasan, C. Cem
Abstract: The fast development of various additive manufacturing processes is motivating research to improve microstructure control during laser assisted treatments, in order to spatially vary material properties on engineering components. In the present work, we demonstrate that a dual-pass laser treatment applied to a low carbon lath martensitic steel can simultaneously repair solidification or fatigue cracks, reduce surface roughness, and, most importantly, trigger phase transformations to create a more damage-resistant microstructure, namely, one that includes interlath austenite. We investigate these influences employing various scanning electron microscopy and transmission high energy X-ray diffraction analyses, mechanical characterization tests, and discuss the underlying mechanisms. Graphical abstract: Image, graphical abstract